Expression of angiogenic factors in sclerosing stromal tumours of the ovary. (4th July 2018) - Hirakawa, Tomoko; Kawano, Yasushi; Mizoguchi, Chiharu; Nasu, Kaei; Narahara, Hisashi
Abstract: Sclerosing stromal tumours (SSTs) are rare benign tumours and are generally observed in individuals in their teens to 20 s. Many cases are suspected as malignant tumours pre-operatively, owing to their high vascularity on diagnostic imaging. Herein, we aimed to evaluate the expressions of various angiogenic factors in SSTs. The expressions of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and hepatocyte growth factor (HGF) were examined by immunohistochemical staining. Upon immunohistochemistry, overexpressions of VEGF, bFGF, and HGF in the ovarian stroma were observed in SSTs. In the normal ovary, the expressions were strong around the vessels and weak in the stroma of the ovary, while a Sertoli–Leydig cell tumour showed weak staining with VEGF, locally strong staining with bFGF and negative staining with HGF. This is the first report about angiogenic factors such as bFGF, and HGF in SST. Impact statement: What is already known on this subject? Sclerosing stromal tumour (SST) is a rare benign tumour with high vascularity. The high vascularity of SSTs are reported to be related to the overexpression of vascular endothelial growth factor (VEGF). But there is no study on the expressions of other angiogenic factors in SST. What do the results this study add? In the immunohistochemical analysis, VEGF, bFGF and HGF were found to be widely stained in SSTs. This results suggest the possibility that the high vascularity seen on diagnostic imaging, and the many small vessels observed microscopically may be related to the expressions of VEGF, bFGF and HGF in SSTs. What are the implications of these findings for clinical practice and/or further research? Our results suggest the possibility that the combined expression pattern of VEGF, bFGF, and HGF may be used as marker of SSTs.